Quasi resonant topology based highly efficient solar-powered induction cooker - Ahmad, Shameem; Awalin, Lilik Jamilatul; Nahid Hasan, Sheikh Md.; Saha, Arghya; Ali, Mohd Syukri; Syafiq, Amirul; Wang, Li (Bulletin of Electrical Engineering and Informatics, 2024)
The energy crisis is a major issue in developing countries, with fossil fuels being the main source of cooking. Induction cookers have received attention due to their safe operation and eco-friendliness, but traditional AC induction cookers are costly and inefficient due to an inverter and rectifier. In this regard, this paper aims to model and develop a solar-powered, low-cost, and highly efficient induction cooker that can be operated directly by solar panels through a battery. By utilizing the solar panels’ maximum output, a maximum power point tracking (MPPT)-based solar power controller has been utilized to charge the battery. A modified coil structure for the cooker is proposed to decrease the coil’s excitation time and increase the resonant frequency. A quasi-resonant converter topology has been used in the proposed induction cooker, as it operates at high frequencies above 20 kHz to avert audible noise and below 100 kHz to minimize losses in switching. The performance of the suggested induction cooktop has been validated by modifying the circuit and the coil of a traditional 220 V, 2 kW induction cooker. Based on the outcomes, it is observed that the efficiency of the proposed induction cooker reached 93%, which is better than that of existing induction cookers.